(untitled) (Issues in Social and Environmental Accounting (ISEA), 2014)
This study examines the strategies companies have adopted in their CSR or non-financial re porting when responding to media criticism related to poor CSR performance. Seven compa nies operation internationally and which have been criticized for irresponsible behavior (like environmental spills, child labor, poor working conditions, corruption, etc.) are identified. The Wilson response model, "Philosophy of Social Responsiveness," which suggests four distinct corporate responses to criticism (Reaction, Defense, Accommodation and Proaction), is ap plied. These four responses occupy a continuum with ‘low response’ on one end and ‘encompassing response’ on the other end. The findings reveal that, in contrast to the Wilson model, which proposes various degrees of response engagement, companies adopted an either/ or response strategy (0-1). They either ignore the criticism (0) or, if they recognize the criti cism (1), they respond in all four of the categories suggested by Wilson. Six of the companies chose the 1 approach. The remaining company chose the 0 response; ignoring the criticism. The 0 response strategy is not presented as an option in the Wilson model, but it is clearly an alternative that companies can take into consideration when evaluating and choosing strategies for non-financial reporting.